Narrativas (auto)biográficas de educadores do SESC SP: discussões sobre o uso das TDIC - Costa, Camila Teixeira (2024)
The present research is part of the Graduate Program in Education: Curriculum of PUC-SP, in the research line New Technologies in Education. It aims to identify how SESC-SP educators articulate with Digital Information and Communication Technologies (DICT) in their workspace, in order to understand if this articulation takes place as a didactic-pedagogical dimension in the context of learning contexts. The proposition of this research deepens studies on digital technologies based on an education that is done in friction with reality. For this, the methodology used is of qualitative approach, having as procedures the bibliographic research, the analysis of documents and the field research. In addition to the bibliography proposed to foster reflection on didactic-pedagogical dimensions in contemporary society, elements of continuing education on the educational practices of educators are presented in a perspective of deepening studies on the non-formal curriculum of SESC-SP. The field research was carried out using the focus group as a reference, under the lens of content analysis. Narratives of seven SESC-SP educators were analyzed through the focus group and the application of a questionnaire. It is understood that the narrative activity contributes to the perception of the reality to which the subject is inserted. This research converges between paths reported on the researcher's life and educators' paths told in dialogue provided by the focus group. Such narrative perspectives present people's lives and express the impossibility of detaching an individual's journey from the social context in which they are inserted, in this way the narratives tell not only the life of educators, but the social, historical and cultural conjuncture of the time lived. This research is strengthened in a counter-hegemonic perspective, highlighting the critical debate around the use and relations of DICT, whether by students and/or educators, as a path of exclusion, domination and oppression in educational spaces, unfolding into a debate aimed at the construction of a necessary dimension for the strengthening of a libertarian and emancipatory education